Nudged elastic band method and density functional theory calculation for finding a local minimum energy pathway of p-benzoquinone and phenol fragmentation in mass spectrometry. Issue 1 (February 2017) - Sugimura, Natsuhiko; Igarashi, Yoko; Aoyama, Reiko; Shibue, Toshimichi
Analysis of the fragmentation pathways of molecules in mass spectrometry gives a fundamental insight into gas-phase ion chemistry. However, the conventional intrinsic reaction coordinates method requires knowledge of the transition states of ion structures in the fragmentation pathways. Herein, we use the nudged elastic band method, using only the initial and final state ion structures in the fragmentation pathways, and report the advantages and limitations of the method. We found a minimum energy path of p- benzoquinone ion fragmentation with two saddle points and one intermediate structure. The primary energy barrier, which corresponded to the cleavage of the C–C bond adjacent to the CO group, was calculated to be 1.50 eV. An additional energy barrier, which corresponded to the cleavage of the CO group, was calculated to be 0.68 eV. We also found an energy barrier of 3.00 eV, which was the rate determining step of the keto-enol tautomerization in CO elimination from the molecular ion of phenol. The nudged elastic band method allowed the determination of a minimum energy path using only the initial and final state ion structures in the fragmentation pathways, and it provided faster than the conventional intrinsic reaction coordinates method. In addition, this method was found to be effective in the analysis of the charge structures of the molecules during the fragmentation in mass spectrometry.